Caracterização da síndrome da dor lombar e fatores associados em trabalhadores rurais expostos a agrotóxicos - Nascimento Filho, Flávio Martins do (2017)
Introduction: Low Back Pain Syndrome is commonly classified as a set of signs and symptoms, of multifactorial origin. Rural work has been currently reported in the scientific literature as one of the most harmful labor practices to human health. Objective: Characterizing low back pain syndrome and associated factors in rural workers exposed to short- to long-term pesticides. Methods: This was an observational, cross-sectional and analytical study in which 322 male rural workers aged 18-59 years old have been exposed to pesticides and the parameters evaluated were: anthropometric characteristics, socio-demographic (marital status, alcoholism and smoking) , acute and chronic pain index in the lumbar spine, hip, knee and ankle through Visual Analog Scale (VAS) and Body Map, as well as functional parameters: body balance through the BERG Balance Scale (BBS), Risk of falls: Time Up and Go Test (TUG TEST) and functionality by OSWESTRY (ODI). The statistical approach was analytical descriptive. Results: Regarding the anthropometric parameters observed: age (34.9 ± 8.4 years), weight (72.9 ± 5.3 kg), height (1.69 ± 0.05) and BMI (24.7 ± 1,9 kg / m²). Most workers n=216 (67.1%) were in the age group of 18-39 years, adequate BMI n=179 (41.9%), time of exposure to pesticides =36 months n=202 (62,7%), predominantly single (n=225) (69.9%), low consumption of tobacco and alcohol respectively, n=193 (59.9%) n=183 (56.8%). It was evidenced that a sample presents acute low back pain n = 219 (66.1%), hip pain n =238 (73.9%) and moderate functional disability n=139 (43.2%). There was a strong correlation between TUG TEST vs. ODI (r= 0.8, p=0.01). Acute low back pain. Age (r=0.8, p=0.01), marital status (r=0.75, p=0.01). Conclusion: The data suggest that rural workers present a higher rate of mild acute low back pain and mild to moderate hip pain, low body imbalance, moderate risk of falls and moderate functional disability.